Sex steroid hormones are associated with mortality in COVID-19 patients: Level of sex hormones in severe COVID-19. Issue 34 (27th August 2021) - van Zeggeren, Ingeborg E.; Boelen, Anita; van de Beek, Diederik; Heijboer, Annemieke C.; Vlaar, Alexander P.J.; Brouwer, Matthijs C.
Abstract : Abstract: In patients with coronavirus disease 2019 (COVID-19), men are more severely affected than women. Multiple studies suggest that androgens might play a role in this difference in disease severity. Our objective was to assess the association between sex hormone levels and mortality in patients with severe COVID-19. We selected patients from the Amsterdam University Medical Centers COVID-19 Biobank, in which patients admitted to hospital in March and April 2020, with reverse transcription-polymerase chain reaction proven severe acute respiratory syndrome-coronavirus-2 infection, were prospectively included. Specifically, we included postmenopausal women (>55 years) and age-matched men, with a mortality of 50% in each group. Residual plasma samples were used to measure testosterone, estradiol, sex hormone binding globulin (SHBG), and albumin. We investigated the association of the levels of these hormones with mortality in men and women. We included 16 women and 24 men in March and April 2020 of whom 7 (44%) and 13 (54%), respectively, died. Median age was 69 years (interquartile range [IQR] 64–75). In men, both total and free testosterone was significantly lower in deceased patients (median testosterone 0.8 nmol/L [IQR 0.4–1.9] in deceased patients vs 3.2 nmol/L [IQR 2.1–7.5] in survivors; P < .001, and median free testosterone 33.2 pmol/L [IQR 15.3–52.2] in deceased patients vs 90.3 pmol/L [IQR 49.1–209.7] in survivors; P = .002). SHBG levels were significantly lower in both men and women who died (18.5 nmol/L [IQR 11.3–24.3] in deceased patients vs 34.0 nmol/L [IQR 25.0–48.0] in survivors; P < .001). No difference in estradiol levels was found between deceased and surviving patients. Low SHBG levels were associated with mortality rate in patients with COVID-19, and low total and free testosterone levels were associated with mortality in men. The role of testosterone and SHBG and potential of hormone replacement therapy needs further exploration in COVID-19. Abstract : Supplemental Digital Content is available in the text